The Relationship between a Toxic Workplace Environment, Workplace Stress, and Employee Development - Al Khoury, Maryana (2022)
Employees are the backbone of every organization. Due to the fast changes in today’s corporate world, it is highly important to take into consideration the employees’ well-being and to keep their stress levels minimized. It is for the organization’s benefit to provide a safe working atmosphere for their employees. Hence, this paper aims to explore the relationship between a toxic workplace environment (TWE), workplace stress (WS), and employee development taking into consideration Career Development and Self-development (EDCD and EDCD). One hundred and twenty-three employees working in the private sector in Lebanon participated in our survey and the results were analyzed using SPSS software. Results indicated that a Toxic Workplace Environment leads to Workplace Stress and Toxic Workplace Environments and Workplace Stress negatively influence Employee Development. Future recommendations and managerial implications of the study are discussed along with limitations.